Agile methods. large-scale development, refactoring, testing, and estimation : XP 2014 International Workshops, Rome, Italy, May 26-30, 2014, Revised Selected Papers - Moe, Nils Brede; Tonelli, Roberto; Counsell, Steve; Gencel, Cigdem; Petersen, Kai; Dingsoyr, Torgeir (Lecture Notes in Business Information Processing, 2014)
This book constitutes the refereed proceedings of three international workshops held in Rome, Italy, in conjunction with the 15th International Conference on Agile Software Development, XP 2014, in May 2014. The workshops comprised Principles of Large-Scale Agile Development, Refactoring & Testing (RefTest 2014), and Estimations in the 21st Century Software Engineering (EstSE21 2014). The 13 revised full papers presented were carefully reviewed and selected from 28 submissions. In addition, an introduction and a keynote paper are included.